effect of foliar feeding with nutrients (N, K, B) and gibberellic acid on the production and specifications of Meyer lemon fruit juice.: تأثير التغذية الورقية بالعناصر الغذائية (N,K,B) وحمض الجبرليك في انتاج ومواصفات عصير ثمار الليمون الحامض الماير (Journal of Hama University, 2024)
This study was conducted in the Bahlouliyeh district of Latakia Governorate during the 2023 agricultural season on lemon trees of the “Mayer” variety, 15 years old and planted at a distance of 4*4 m. With the aim of studying the effect of foliar feeding with nutrients (N, K, B) and gibberellic acid GA3 on some chemical specifications of fruit juice. Four chemical compounds were used in foliar spraying: urea, potassium sulfate, boron, and gibberellic acid, individually and together, at different concentrations (2.5 g/l, 1.5 g/l, 200 ppm, 20 ppm) respectively. The results of the statistical analysis showed that the spraying treatment with the four compounds combined (GA3, N, B, and K) was superior to the other treatments in terms of the percentage of total dissolved solids (10.08%), followed by the two spraying treatments with boron and urea (9.20%), compared with the control (6.26). %). The results of the statistical analysis also showed that the spraying treatment with the four compounds combined (GA3, N, B, and K) was superior to the other treatments in terms of total acidity, reaching (6.36%), compared to the control (3.63%). The results also showed that the two foliar spray treatments with the four compounds combined (GA3, N, B, and K) and the spray treatment with boron and urea were superior to all other treatments in terms of the percentage of vitamin C, reaching (52.33%) and (51.26%), respectively, compared to the control ( 22.5%). The results also showed that the spraying treatment with the four compounds combined (GA3, N, B, and K) was superior to all other treatments in terms of the percentage of total sugars and amounted to (3.54%), compared to the control (2.17%). The results also showed that the spraying treatment with the four compounds combined (GA3, N, B, and K) was superior to all other treatments in terms of productivity, reaching (77.09 kg/tree) compared to the control (43.55 kg/tree).
Keywords: Keywords: foliar nutrition, Meyer variety, total acidity, total soluble solids, vitamin C, total sugars